2022
DOI: 10.26434/chemrxiv-2022-ml80t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reference Raman Spectrum and Mapping of Cryptosporidium parvum Oocysts

Abstract: Cryptosporidium parvum is a protozoan parasite and among the most infectious diarrhea-causing pathogens, leading to severe health problems for malnourished children and immunocompromised individuals. Outbreaks are common even in developed countries, originating from water or food contamination and resulting in suffering and large costs for society. Therefore, robust, fast and highly specific detection strategies of Cryptosporidium are needed. Label-free detection techniques such as Raman spectroscopy have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Optical tweezers have been used extensively to characterize and assess spore mechanisms on an individual level [9, 20–26], but the number of studies detailing the impact laser trapping has on the spore is limited. In a recent work, it was shown that optical tweezers could cause structural changes at high dose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Optical tweezers have been used extensively to characterize and assess spore mechanisms on an individual level [9, 20–26], but the number of studies detailing the impact laser trapping has on the spore is limited. In a recent work, it was shown that optical tweezers could cause structural changes at high dose levels.…”
Section: Introductionmentioning
confidence: 99%